A survey of the knowledge of tourists or guests about Shariah-compliant homestay facility services in Sabah - Suhailah Abdul Muin; Mohd. Nor Azan Abdullah; Norcikeyonn Samuni (Human Resource Management Academic Research Society (HRMARS), 2024)
This research aimed to examine tourists' or guests' knowledge of the services of Shariahcompliant homestay accommodation facilities in Sabah. This study was conducted to determine guests' knowledge about the concept of Shariah-compliant homestays, the facilities provided, and their perception of the experience of staying there. Therefore, several questions materialised, such as the extent to which tourists or guests understand the concepts and principles of Shariah-compliant homestays. This investigation was performed online (Google Survey Form) and involved 260 respondents. Data were presented as mean scores and frequencies (percentages) analysed using the Statistical Package for Social Sciences (SPSS). Of the 13 variables related to the knowledge of tourists or guests regarding Shariah-compliant accommodation facilities in Sabah, 12 of them reached a high level, preceded by knowledge of Shariah-compliant homestay accommodation providing the Quran, prayer rugs and Qibla direction signs with a total mean score of 4.26. Meanwhile, only one variable reached the moderate level: the knowledge of the status of the number of Shariah-compliant accommodation facilities offered in Sabah, with a mean score value of 2.96. Ultimately, the conclusions can guide homestay operators, local authorities, and other stakeholders in ameliorating guests' understanding and grasp of Sharia-compliant homestays.